Early Rivaroxaban Use After Cardioembolic Stroke May Not Result in Hemorrhagic Transformation: A Prospective Magnetic Resonance Imaging Study. Issue 7 (July 2016) - Gioia, Laura C.; Kate, Mahesh; Sivakumar, Leka; Hussain, Dulara; Kalashyan, Hayrapet; Buck, Brian; Bussiere, Miguel; Jeerakathil, Thomas; Shuaib, Ashfaq; Emery, Derek; Butcher, Ken
Abstract : Background and Purpose—: Early anticoagulation after cardioembolic stroke remains controversial because of the potential for hemorrhagic transformation (HT). We tested the safety and feasibility of initiating rivaroxaban ⩽14 days after cardioembolic stroke/transient ischemic attack. Methods—: A prospective, open-label study of patients with atrial fibrillation treated with rivaroxaban ⩽14 days of transient ischemic attack or ischemic stroke (National Institute of Health Stroke Scale <9). All patients underwent magnetic resonance imaging <24 hours of rivaroxaban initiation and day 7. The primary end point was symptomatic HT at day 7. Results—: Sixty patients (mean±SD age 71±19 years, 82% stroke/18% transient ischemic attack) were enrolled. Median (interquartile range) time from onset to rivaroxaban was 3 (5) days. At treatment initiation, median National Institute of Health Stroke Scale was 2 (4), and median diffusion-weighted imaging volume was 7.9 (13.7) mL. At baseline, HT was present in 25 (42%) patients (hemorrhagic infarct [HI]1=19, HI2=6). On follow-up magnetic resonance imaging, no patients developed symptomatic HT. New asymptomatic HI1 developed in 3 patients, and asymptomatic progression from HI1 to HI2 occurred in 5 patients; otherwise, HT remained unchanged at day 7. Conclusions—: These data support the safety of rivaroxaban initiation ⩽14 days of mild–moderate cardioembolic stroke/transient ischemic attack. Magnetic resonance imaging evidence of petechial HT, which is common, does not appear to increase the risk of symptomatic HT. Abstract : Supplemental Digital Content is available in the text.